Raw material origin and preference of the Lärbro Group, Tjängvide Group and D-type picture stones at Statens Historiska Museet in Stockholm, Sweden - Hänsel, Patrick; Wendt, Antje; Oehrl, Sigmund; Munnecke, Axel (GFF, 2025)
The Lärbro Group and Tjängvide Group are two special groups of picture stones from Gotland, Sweden. They are characterised by their motifs and decorations. The picture stones of the Lärbro Group seem to belong to the same tradition of one group of crafters, whereas the picture stones of the Tjängvide Group were probably produced by the same crafter. In this study, we present the carbon (δ13C) and oxygen (δ18O) isotope values, and visual facies analyses of the raw material, which were carried out on five sampled picture stones of the Lärbro Group and three sampled picture stones of the Tjängvide Group at Statens Historiska Museet in Stockholm, Sweden. The crafters mainly used local materials from single geological units, Slite Group and Hemse Group, to produce picture stones. In addition, we determine possible transport distance minima up to 10 km between the raw material source area and the find place of the analysed picture stones. Finally, we present that coarse and fine reef debris limestones were preferred by the crafters for producing those picture stones.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Carbon isotopes; facies analysis; Gotland; Iron Age; oxygen isotopes; raw material preference; transport distances

Stable carbon and oxygen isotope geochemistry as provenance indicator for the picture stones on Gotland (Sweden) - Hänsel, Patrick; Oehrl, Sigmund; Ideström, Lena; Widerström, Per; Reddin, Carl James; Munnecke, Axel (GFF, 2023)
The picture stones from Gotland are one of the most famous and exceptional groups of monuments known from Swedish Prehistory. These carved memorial stones and their extraordinarily rich imagery are a unique source for the study of Late Iron and Viking Age culture and in particular Scandinavian pre-Christian religions. The Gotlandic picture stones are mainly made from the thickly layered limestones surrounding the reefs and bioherms of Gotland’s carbonate platform from the middle part of the Silurian (latest Llandovery to Ludlow, Telychian–Ludfordian). However, the exact origins of the picture stones’ raw materials on Gotland have remained undetermined. In this paper, we investigate the geological origin of the raw material by isotope geochemistry. Whereas the oxygen (δ18O) and strontium isotope ratio (87Sr/86Sr) were strongly altered by diagenesis the carbon isotope ratio (δ13C) is quite stable. Because the different geological units on Gotland show specific isotope signatures, the δ13C values from picture stones can be used to assign them to the respective geological unit, and thus to the source area of the raw material. This also allows for an estimation of transport distance minima between the raw material source area and the find place of each sampled picture stone. Most of the picture stones seem to be produced from local material with short transport distances, less than 10 km and only a few were transported at a far distance exceeding 10 km. In summary, the transport distance was dependent mostly on the local availability of picture-stone-suitable rocks.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Carbon isotopes; Gotland; Iron Age; oxygen isotopes; picture stones; strontium isotopes; transport distances

The raw material preferences for producing picture stones on Gotland - Hänsel, Patrick; Oehrl, Sigmund; Widerström, Per; Ideström, Lena; Munnecke, Axel (Fornvännen. Journal of Swedish Antiquarian Research, 2024)
The picture stones on Gotland are monuments from the late Scandinavian Iron Age, which are important for the archaeological research about the North Germanic culture. Their imagery is also a valuable source for the pre-Christian religion in Scandinavia. Most of them are produced of Silurian limestones which are dated 423 to 433 million years. The Gotlandic picture stones were produced of thickly bedded limestones which are exposed in the vicinity of fossil reefs and carbonate platforms. Archaeologically, the picture stones can be classified into five groups (A to E stones), and an informal sixth group (so-called blind C/D/E stones). Geologically, the picture stone raw materials can be sorted into six different types based on visual facies analysis. The purpose of our paper is to investigate the raw material preferences for single picture stone types. According to our results, coarse and fine reef debris limestones were the most frequently used rock types. For the B stones, crinoidal limestone was preferentially used because of its sparkling effect of the crinoid remains in sunlight. However, the availability of nearby thickly bedded limestones was the most important prerequisite to produce most of the picture stone
Keywords: crinoidal limestone; Gotland; picture stones; raw material preferences; reef debris limestone